Individual Wealth Inequality : Measurement and Evidence from Low- and Middle-Income Countries - Hasanbasri, Ardina; Kilic, Talip; Koolwal, Gayatri; Moylan, Heather (World Bank, Washington, DC, 2022)
The accumulation of personal wealth, stemming from ownership and control of assets, plays a critical role in advancing women’s and men’s economic opportunities. Yet, it is an understudied dimension of inequality across the developing world. To study individual-level wealth inequality and gender differences in wealth, this paper leverages unique data from nationally representative, multi-topic household surveys that were conducted in Cambodia, Ethiopia, Malawi, and Tanzania and that interviewed men and women in private regarding their personal ownership and valuation of physical and financial assets. The analysis documents substantial gender inequalities in asset ownership and wealth, overall and for specific asset classes. Individual-level wealth inequality measures are substantially higher vis-à-vis comparators based on per capita household consumption expenditures and per capita household wealth, and intrahousehold wealth inequality has a substantial role in explaining overall wealth inequality. While land is a key contributor to wealth inequality across countries, there is cross-country heterogeneity in the relative contributions of asset classes. Self-reporting on asset ownership and valuation, the internationally-recommended best practice, is also shown to lead to higher inequality estimates compared to the business-as-usual survey practice of interviewing a single, most-knowledgeable household member to identify intrahousehold asset owners and values. The discussion expands on the implications of the findings for future surveys and methodological research.